2017
DOI: 10.1177/1010428317694321
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide gastrin-releasing peptide induces PI3K/reactive oxygen species–dependent migration in lung adenocarcinoma cells

Abstract: Nerve fibers and neurotransmitters have increasingly been shown to have a role in tumor progression. Gastrin-releasing peptide is a neuropeptide linked to tumor aggressiveness, acting as an autocrine tumor growth factor by binding to its receptor, gastrin-releasing peptide receptor, expressed by many tumors. Although neuropeptides have been previously linked to tumor cell proliferation, more recent studies have uncovered roles for neuropeptides in chemotaxis and metastasis. Understanding the precise roles of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
(86 reference statements)
0
4
1
Order By: Relevance
“…Therefore, we suggest that the alveolar epithelium is not a target for GRP in order to get a fibrotic response in the lung via EMT. Jaeger and colleagues reported that GRP had no proliferative effect on A549 cells on 24 h after GRP (50 and 100 nM) administration, but it stimulated ROS production and cell migration of these cells [30]. However, it has been shown for the first time that GRP application causes the proliferation of A549 cells in the present study.…”
Section: Discussioncontrasting
confidence: 77%
“…Therefore, we suggest that the alveolar epithelium is not a target for GRP in order to get a fibrotic response in the lung via EMT. Jaeger and colleagues reported that GRP had no proliferative effect on A549 cells on 24 h after GRP (50 and 100 nM) administration, but it stimulated ROS production and cell migration of these cells [30]. However, it has been shown for the first time that GRP application causes the proliferation of A549 cells in the present study.…”
Section: Discussioncontrasting
confidence: 77%
“…Thus, the GRK5 KD hampers the autocrine signalling mechanism by inhibiting the expression of both the endogenous ligand as well as that of the corresponding receptor. GRPR is the sole receptor involved in the chemotaxis of cancer cells towards the ligands GRP/bombesin 29,30 . The decrease in its expression by GRK5 KD therefore directly impacts the migration of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the lung, GRP is produced by specialized epithelial cells, pulmonary neuroendocrine cells, that are activated by neuronally derived γ -aminobutyric acid (GABA) to form clusters called neuroendocrine bodies (NEB) that secrete GRP. GRP binds to its receptor, GRPR (BB2), and activates downstream signal transduction pathways ( e.g ., cAMP, MAPK, PI3K, Akt) ( 93 , 94 ). GRP synergizes with LPS for cytokine production by macrophages ( 82 ).…”
Section: A Central Role For Damp-mediated Tlr4 Signaling In Acute Lung Injury (Ali) Caused By Influenza Infectionmentioning
confidence: 99%